Development of a web-based single-phase load monitoring and auditing system - Oluwaseun Ibrahim Adebisi; Isaiah Adediji Adejumobi; Simeon Matthew; Azeez Aderibigbe Abdulsalam (Institute of Advanced Engineering and Science, 2022)
In a developing nation like Nigeria, the conventional load monitoring and billing system has proved to be tedious, time-consuming, expensive, and prone to human error over the years. Therefore, this creates the need for an efficient system that can assist the Utility to monitor the energy consumption trend of the customers remotely. This work developed a web-based single-phase load monitoring and auditing system using NodeMCU (ESP8266) microcontroller, PZEM-004T sensor, and liquid crystal display (LCD) module for the hardware unit and Blynk internet of things (IoT) platform for the software unit. The system design was implemented around the ESP8266 microcontroller with relevant design models, and standard power and energy equations programmed into the microcontroller in the Arduino integrated development environment. The developed system was load tested to examine its performance and determine its reading error. The hardware and software units of the system operated satisfactorily when tested. The reading accuracy for current and voltage measured by the device were ±0.2% and ±0.4%, respectively, giving a reading error of ±0.8% for power measurement. The developed system is suitable for residential, commercial, and similar applications where the energy usage trend of some small loads is required for management purposes.